Molecular diversity of fungal endophytes isolated from Garcinia mangostana and Garcinia parvifolia. - Sim, Jiun-Horng; Khoo, Chai-Hoon; Lee, Learn-Han; Cheah , Yoke Kqueen (The Korean Society for Applied Microbiology, 2010)
Garcinia is commonly found in Malaysia, but limited information is available regarding endophytic fungi associated with this plant. In this study, 24 endophytic fungi were successfully recovered from different parts of two Garcinia species. Characterization of endophytic fungi was performed based on the conserved internal transcribed spacer (ITS) region sequence analysis and the antimicrobial properties. Results revealed that fruits of the plant appeared to be the highest inhabitation site (38%) as compared with others. Glomerella sp., Guignardia sp., and Phomopsis sp. appeared to be the predominant endophytic fungi group in Garcinia mangostana and Garcinia parvifolia. Phylogenetic relationships of the isolated endophytic fungi were estimated from the sequences of the ITS region. On the other hand, antibacterial screening showed 11 of the isolates possessed positive response towards pathogenic and nonpathogenic bacteria. However, there was no direct association between certain antibacterial properties with the specific genus observed.